STUDI KASUS PROSEDUR PEMERIKSAAN RADIOGRAFI VERTEBRAE THORACOLUMBAL DENGAN KLINIS SKOLIOSIS DI INSTALASI RADIOLOGI RSUD KARANGANYAR - Mahanani, Ayu; Prabowo, Bagus waskito; Fakhrurreza, Muhammad; Faesol, Ahmad (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The radiographic examination technique of the Thoracolumbar Vertebrae with scoliosis cases consists of right and left bending Anterior posterior (AP), Lateral, and Anterior Posterior (AP) projections, as well as the addition of the Ferguson method and fulcrum projection. The procedure for scoliosis examination at radiology installation in RSUD (Regional Hospital) Karanganyar is unknown, so it is necessary to do research to find out the examination procedure and the effectiveness of using these projections. This study aims to determine the procedure for radiographic examination of thoracolumbar vertebrae with clinical scoliosis at the Radiology Installation of RSUD Karanganyar. This research is qualitative research with a case study approach. The data collection method included observing scoliosis examination which included preparation of tools and materials, patient preparation, and examination techniques, then reinforced by interviews with radiographers and doctors to find out the procedures and reasons for using these projections. The results of observations and interviews were analyzed by means of data reduction, data presentation, then conclusions were drawn. The results of the study showed that the thoracolumbar vertebrae examination procedure with clinical scoliosis in Radiology Installation of RSUD Karanganyar used the AP and Lateral projection technique. The reason for using AP and Lateral projections was because these projections served as initial screening for scoliosis patients and could already establish a diagnosis. Both projections provided a smaller dose of radiation received by the patient and were in accordance with the request of the sending doctor. It is advisable for further examination of the thoracolumbar vertebrae with clinical scoliosis add the right and left bending projections and Ferguson, because it aims to provide information that cannot be seen from the AP and lateral projections.